Retrograde type A aortic dissection: a different evil. (22nd October 2022) - Lopez-Marco, Ana; Adams, Benjamin; Oo, Aung Ye
Abstract: Retrograde type A aortic dissection (RTAAD) can be spontaneous or secondary to the instrumentation of the descending and thoraco-abdominal aorta. It has anatomical differences compared to antegrade type A aortic dissection that impact the management and prognosis. Treatment is not standardized. We report our approach to spontaneous RTAAD in our institution between 2018 and 2022 ( n = 15). The mean age was 60.1 years and 93% were male. Aortic valve, coronary arteries and supra-aortic trunks were spared by the dissection in 80% of the cases; distal extension to iliacs was common and lower limb malperfusion was present in 4 cases (27%). The ascending aorta was dilated at presentation in 60% of the cases. Emergency surgery with arch/FET replacement was offered to 11 patients (73%); 3 patients (20%) received a limited proximal aortic repair; 1 patient was treated conservatively. Overall mortality was 47% (100% for limited proximal repair and 22% for those who received arch/FET). We advocate for aggressive treatment of RTAAD excluding the primary entry tear to prevent immediate- and mid-term complications. Abstract : Retrograde type A aortic dissections (RTAAD) are less frequent than the antegrade type A form, where the primary entry tear is located within the root, ascending and/or arch of the aorta and the dissection propagates antegradely into the distal aorta.